PENGARUH METODE MIND MAPPING PADA TEMA 5 MATERI PENGELOMPOKAN HEWAN TERHADAP HASIL BELAJAR KELAS V SDIT SALSABILA 6 MAGETAN - Alfi Aturrohmah; Sofyan Susanto; Prima Rias Wana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
The mind mapping method is expected to make it easier for students to understand the subject matter. Therefore, researchers conducted research at SDIT Salsabila 6 Magetan grade 5 on the effect of the mind mapping method on theme 5 of animal grouping material. This study uses an experimental method with a Non-Equivalent control group design. The average value of the experimental class is higher than the average value of the control class. With the number of N experimental class 20 and control class 20. In the experimental class tcount> t table = 2,591> 1,529 means a significant effect. If tcount > t table then H0 is rejected and Ha is accepted. H0 defines that there is no effect of the mind mapping method on student learning outcomes and Ha defines that there is an effect of the mind mapping method on student learning outcomes. Information sig.(2-tailed) also obtains 0.02 where if sig < 0.05 then H0 is rejected and Ha is accepted. H0 defines that there is no effect of the mind mapping method on student learning outcomes and Ha defines that there is an effect of the mind mapping method on student learning outcomes. It can be concluded that the results of sig. (2-tailed) < 0.05 then the hypothesis defines that there is an effect of the mind mapping method on student learning outcomes.